Apolipoprotein A-I Limits the Negative Effect of Tumor Necrosis Factor on Lymphangiogenesis. Issue 11 (November 2015) - Bisoendial, Radjesh; Tabet, Fatiha; Tak, Paul P.; Petrides, Francine; Cuesta Torres, Luisa F.; Hou, Liming; Cook, Adam; Barter, Philip J.; Weninger, Wolfgang; Rye, Kerry-Anne
Abstract : Objective—: Lymphatic endothelial dysfunction underlies the pathogenesis of many chronic inflammatory disorders. The proinflammatory cytokine tumor necrosis factor (TNF) is known for its role in disrupting the function of the lymphatic vasculature. This study investigates the ability of apolipoprotein (apo) A-I, the principal apolipoprotein of high-density lipoproteins, to preserve the normal function of lymphatic endothelial cells treated with TNF. Approach and Results—: TNF decreased the ability of lymphatic endothelial cells to form tube-like structures. Preincubation of lymphatic endothelial cells with apoA-I attenuated the TNF-mediated inhibition of tube formation in a concentration-dependent manner. In addition, apoA-I reversed the TNF-mediated suppression of lymphatic endothelial cell migration and lymphatic outgrowth in thoracic duct rings. ApoA-I also abrogated the negative effect of TNF on lymphatic neovascularization in an ATP-binding cassette transporter A1-dependent manner. At the molecular level, this involved downregulation of TNF receptor-1 and the conservation of prospero-related homeobox gene-1 expression, a master regulator of lymphangiogenesis. ApoA-I also re-established the normal phenotype of the lymphatic network in the diaphragms of human TNF transgenic mice. Conclusions—: ApoA-I restores the neovascularization capacity of the lymphatic system during TNF-mediated inflammation. This study provides a proof-of-concept that high-density lipoprotein–based therapeutic strategies may attenuate chronic inflammation via its action on lymphatic vasculature. Abstract : Supplemental Digital Content is available in the text.